Violence and vengeance religious conflict and its aftermath in eastern Indonesia - Duncan, Christopher R. (Cornell University Press, 2013)
Christopher R. Duncan spent several years conducting fieldwork in North Maluku, and in Violence and Vengeance, he examines how the individuals actually taking part in the fighting understood and experienced the conflict.